MENDEKONSTRUKSIKAN FILSAFAT ILMU DALAM ILMU AKUNTANSI GLOBAL - Lestari, Yona Octiani (IQTISHODUNA, 2013)
" Accounting is built in a civilization, accounting developments influenced by social relationshipsbetween people. Accounting development is strongly influenced by particular purpose. There are severalobjective is political purpose, social purpose, economic purpose, objectives and purpose of cultural ideology.Accounting accounting today is filled with all the goals. Accounting has been fused with the capitalist,because accounting kapitali developing countries. Capitalist accounting notch higher and more generalized.And now there should be a study of true science. Where accounting is at the smallest of partial science. Thesource of all science is actually contained in the Al-Qur’an. Islamization of science is an attempt to makeMuslims do not just accept and imitate the methods of the method offered by western nations, namely theknowledge on how to restore its center is monotheism. Of monotheism will be three kinds of unity is the unityof knowledge, the unity of life and unity history.